Biochemical composition changes of gram-negative microorganisms under the action of new chemical compounds (One Health & Risk Management, 2021)
Introduction. It is known that the enzymes catalase (CT) and superoxide dismutase (SOD) are actively involved in protecting cells of microbial pathogens against the biochemical factors produced by macrophages in vivo, in order to stop infection. Therefore, this study was aimed to quantify the parameters of the antioxidant-enzyme activities within the reference cultures under the action of selected new chemical compounds.Material and methods. Cu (II) coordination compounds, Co (II) and Zn (II) were included as “in vitro” study material, as well as aromatic propenones synthesized at the Department of Inorganic Chemistry, at State University of Moldova. The antimicrobial effects were tested on three gram-negative reference strains. The enzymatic activity of SOD and the CT activity was determined to assess the pathogen-induced changes in the antioxidant status under the action of newly tested compounds.Results. The new chemical compounds showed a significant decrease in the antioxidant enzymatic activities of SOD and CT, induced in all reference strains used, which indicates an intense oxidative stress generated by the tested compounds.Conclusions. The specific activity of new chemical compounds on primary antioxidant enzymes, which represent pathogenicity factors of infectious agents, allows us to assume the benefits of in vivo effect of new native substances, as well as to recommend the selected compounds for further biomedical tests.